Splenic lymphoma in an adult local bitch: a case report (2002)
A four-year old local dog weighing 12kg was presented four days after signs of persistent anorexia and dullness were observed. Physical examination of the bitch revealed a circumscribed distension of the left lateral abdomen about 5cm caudal to the rib cage, which on palpation appeared firm, discrete and nodular but painless. X-rays views confirmed that the mass was intrasplenic and had a fat density. Blood and urine samples were analysed, the result of which showed proteinuria, bilirubinuria and neutrophilic leucocyosis. Exploratory laparotomy and spleenectomy were carried out. The extirpated spleen had pendunculated projection. The biopsy of the spleen revealed that the tumour is a lymphoma